Exercise intensity regulates the effect of heat stress on substrate oxidation rates during exercise. Issue 7 (8th August 2020) - Maunder, ED; Plews, Daniel J.; Merien, Fabrice; Kilding, Andrew E.
Abstract: Hyperthermia stimulates endogenous carbohydrate metabolism during exercise; however, it is not known if exercise intensity impacts the metabolic effect of heat stress. In the first study of this two-part investigation, endurance-trained male cyclists performed incremental exercise assessments in 18 and 35°C (60% rH). The stimulatory effect of heat stress on carbohydrate oxidation rates was greater at high vs. moderate vs. low relative intensity ( P < 0.05). In agreement, no effects of heat stress on carbohydrate oxidation rates were observed during 60-min of subsequent low-intensity cycling. In study two, endurance-trained male cyclists performed 20-min of moderate-intensity (power at the first ventilatory threshold) and 5-min of high-intensity (power at the second ventilatory threshold) cycling in 18, 28, 34, and 40°C (60% rH). At moderate-intensity, carbohydrate oxidation rates were significantly elevated by heat stress in 40°C ( P < 0.05), whereas at high-intensity carbohydrate oxidation rates were significantly elevated by heat stress in 34 and 40°C ( P < 0.05). This exercise intensity-mediated regulation of the effect of heat stress on carbohydrate oxidation may be partially attributable to observed plasma adrenaline responses. Our data suggest that under moderate environmental heat stress (34–35°C, 60% rH), heat stress-induced changes in CHO oxidation rates are unlikely to occur unless the relative exercise intensity is high (81 ± 8%⩒O2max ), whereas under more extreme environmental heat stress (40°C, 60% rH), these changes occur at lower relative intensities (69 ± 8%⩒O2max ). This provides indication of when heat stress-induced metabolic changes during exercise are likely to occur.